Stock liquidity and stock price crash risk: Evidence from Vietnam - Ngoc Bao Dinh; Hy Nguyen Song Tran (Cogent Business & Management, 2023)
This research examines whether stock liquidity affects the crash risk of stock price for companies listed on the Vietnamese stock market. Using a comprehensive dataset encompassing all stocks listed on the Ho Chi Minh Stock Exchange (HOSE) and the Hanoi Stock Exchange (HNX) from 2010 to 2022, we find that stock liquidity has a negative impact on stock price crash risk. Our findings are consistent with governance theory, which considers stock liquidity as a governance mechanism to discipline managers for hiding negative information, that could lead to stock price crashes. To the best of our knowledge, our paper is one of the initial studies to provide evidence regarding the impact of stock liquidity on stock price crash risk in the context of Vietnam. Thus, this study significantly contributes to the research literature on stock liquidity and crash risk in emerging markets. Furthermore, this research provides valuable insights for policymakers, authorities, managers, and investors, offering potential strategies for managing the crash risk of stock price.
Keywords: 650; governance mechanism; regression model; stock liquidity; stock price crash risk